Antibacterial Effects of Chitosan Monosaccharides Complex on Pathogens in Snakehead Fish Surimi as Food Matrix Model - Shanti Dwita Lestari; Ace Baehaki; Reny Meliza (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
The complex formed between chitosan and sugar as a result of heating process which induces the Maillard reaction is known to have antibacterial and antioxidant properties. This study aims to compare the antibacterial activity of chitosan monosaccharide complexes against Bacillus subtilis, Listeria monocytogenes and Vibrio cholera in snakehead fish surimi as the food matrix model. The analysis was conducted onthe color intensity of the Maillard Reaction Products (MRPs) which was formed through the reaction of chitosan with glucose, galactose and fructose. The antibacterial activity of each MRPs was studied both invitro and in the food matrix using disc difussion and standard plate count method respectively. The results showed that the chitosan galactose complex had the highest color intensity with absorbance values at 420nm of 0.248. In vitro tests result showed that the chitosan glucose complex had the greatest inhibition on all three test bacteria. Whereas, when MRPs was applied in the food matrix of snakehead fish surimi, thegalactose chitosan complex showed the best inhibitory effect against B. subtilis and L. monocytogenes with a decrease in the number of bacteria of 0.63 and 2.13 log CFU/mL respectively compared to the control.On the other hand, the inhibitory activity of V. cholera in the food matrix was effectively performed by the glucose chitosan complex with the total bacterial count of 2.25 log CFU/mL l lower than the control. The addition of chitosan and chitosan monosaccharide complex to the food matrix generally reduced the total microbial count (TPC) by 1.53 log CFU/mL. This result confirms that the antibacterial activity of MRPs isconsistent .both in vitro and in the food matrix.